Using Automata in Control Synthesis. A Case Study - Hune, Thomas S.; Sandholm, Anders B. (BRICS Report Series, 2000)
We study a method for synthesizing control programs. The method merges an existing control program with a control automaton. For specifying the control automata we have used monadic second order logic over strings. Using the Mona tool, specifications are translated into automata. This yields a new control program restricting the behavior of the old control program such that the specifications are satisfied. The method is presented through a concrete example.